Hate Speech: Commentary Analysis on Celebrity Instagram Accounts Based on Prophetic Communication - Maya Amalia Oesman Palapah; Ratri Rizki Kusumalestari; Riza Hernawati; Ferry Darmawan (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
Social media has seamlessly integrated into the daily lives of countless individuals, captivating users who spend significant portions of their time scrolling through their feeds and interacting with their online connections. This digital era, however, has brought to light a darker side – the prevalence of hate speech and abusive behavior, notably among Indonesian netizens. This study seeks to identify and scrutinize official Instagram accounts of certain celebrities, focusing on the presence of hate speech. Employing a quantitative research method with content analysis, the research centers on comments made by fans. Data will be gathered, coded, and subjected to a reliability test for categorization. The findings underscore a disturbingly high incidence of hate speech on Instagram accounts, highlighting the need for intervention from multiple stakeholders, particularly within the realms of communication science and prophetic communication. This research offers invaluable insights into social media usage and paves the way for corrective measures, education, and evaluation, ultimately striving to foster a more positive and constructive social media environment for all users.